Predicting Employee Performance by Leadership, Job Promotion, and Job Environmental in Banking Industry - Sindy Cahya Febrina (Jurnal Keuangan dan Perbankan, 2017)
This study aimed to analyze the effect of leadership, job promotion and job environmental simultaneously or partially had the effect on employee performance in Bank UMKM East Java Malang Branchand to analyze the variable that dominant influenced from leadership, job promotion and job environmentalon employee performance. The population of this research was all 32 employees Bank UMKM branch Malang. The technique of sampling by saturated sampling, the technique through determined all populationmembers as a sample, so the numbers of sample in this research were 32 employees. Data collection by questioners, than the data was analyzed by SPSS programs through multiple linier regressions analyzed. The result of research indicated that leadership variable, job promotion and job environmentalsimultaneously had significant effect on bank employee performance. Leadership variable, job promotion and job environmentalpartially had had significant effect on bank employee performance and job promotion had dominant effect on bank employee performance.